Acute kidney injury following high-dose vitamin C treatment - Andres, Annick; Zeier, Martin; Eckert, Christoph (Deutsches Ärzteblatt, 2019)
A 63-year-old man was admitted to our department with oliguric acute kidney injury 2 months after resection of ductal pancreatic cancer. The patient was a veterinarian and took an interest in alternative medicine. Serum creatinine, normal the week before, was measured at 8.2 mg/dL. Renal biopsy revealed osmotic tubulopathy (Figure, red asterisk) and extensive tubulointerstitial deposits of oxalate crystals (Figure, black asterisk). On questioning, the patient reported self-administration of intravenous high-dose ascorbic acid (veterinary preparation, dose unknown, contamination/damage not excluded). High-dose vitamin C is widely used as an adjuvant treatment for tumors in complementary medicine, despite the lack of reliable evidence for its efficacy. There are also indications that it may be effective in patients with sepsis or severe burns and in the context of coronary heart surgery. However, more research is required. Ascorbic acid dissolves in water and is therefore thought to be relatively safe. Acute kidney damage, especially with pre-existing kidney injury, is a rare but known adverse effect. Our patient’s oliguria persisted, so hemodialysis was started. Dialysis was successfully discontinued 2 months later.